2020
DOI: 10.3892/etm.2020.8415
|View full text |Cite
|
Sign up to set email alerts
|

miR-130a alleviates neuronal apoptosis and changes in expression of Bcl-2/Bax and caspase-3 in cerebral infarction rats through PTEN/PI3K/Akt signaling pathway

Abstract: Effect of micro ribonucleic acid (miR)-130a on neuronal apoptosis in rats with cerebral infarction (CI) was studied to explore whether phosphatase and tensin homolog deleted on chromosome ten (PTEN)/phosphatidylinositol 3-hydroxy kinase (PI3K)/protein kinase B (Akt) is involved in the regulation of neuronal apoptosis. Thirty-six Sprague-Dawley (SD) rats were randomly divided into blank control group, model group and miR-130a low-expression group. miR-130a was determined by quantitative polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In comparison to healthy individuals, some age-related neurodegenerative diseases such as Alzheimer’s disease and spinocerebellar ataxia type 1 were associated with the increased expression of miR-101, miR-130, and miR-144 in the cerebellum and cortex [ 108 ]. The up-regulation of miR-130a was also found in the brain tissues of rats with cerebral infarction and was correlated with subsequent elevated neuronal apoptosis, accompanied by the liberation of inflammatory mediators and the inhibition of the PTEN/PI3K/Akt signaling pathway and anti-apoptotic genes [ 109 ].…”
Section: Micrornas As Aging Biomarkersmentioning
confidence: 99%
“…In comparison to healthy individuals, some age-related neurodegenerative diseases such as Alzheimer’s disease and spinocerebellar ataxia type 1 were associated with the increased expression of miR-101, miR-130, and miR-144 in the cerebellum and cortex [ 108 ]. The up-regulation of miR-130a was also found in the brain tissues of rats with cerebral infarction and was correlated with subsequent elevated neuronal apoptosis, accompanied by the liberation of inflammatory mediators and the inhibition of the PTEN/PI3K/Akt signaling pathway and anti-apoptotic genes [ 109 ].…”
Section: Micrornas As Aging Biomarkersmentioning
confidence: 99%
“…Overexpression of TM4SF1 significantly activated the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway, which acts through the downstream apoptosis-related proteins B-cell lymphoma 2 (Bcl2), BCL-2 associated X (Bax), caspase-3, and caspase-9 to induce anti-apoptotic effects in breast cancer ( Sun et al, 2015 ; Wei et al, 2018 ). Bcl2 and Bax are members of the Bcl2 family, which are key regulators of apoptosis ( Wang et al, 2020 ). Bcl2 inhibits apoptosis by preventing cytochrome c release from the mitochondria into the cytoplasm.…”
Section: Tm4sf1 Promotes Cancer Proliferation and Migrationmentioning
confidence: 99%
“…Elevated expression of Bax is usually associated with apoptosis, while decreased expression levels of Bcl-2 demonstrate a reduced ability to inhibit apoptosis (33). Bax is a pro-apoptotic member of the Bcl-2 family and it is closely related to PI3K pathway (33,34). Molton et al (35) found that CC139 fibroblasts treated with PI3K inhibitors showed a downregulation of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%